PENGARUH FAKTOR DEMOGRAFIS PADA ADOPSI LAYANAN BERBASIS TEKNOLOGI PADA PERBANKAN SYARIAH - Nuri Wulandari (Jurnal Ilmu Manajemen & Ekonomika, 2015)
Mobile phone and internet users in Indonesia continues to grow rapidly. It utilized by the bank to provide technology-based services, so that customers can trade without restriction of place and time. However, like other technologies, customers require adjustment for the adoption of such technology-based services. One of the factors that affect the adoption of technology-based service is the customer demographics.This study investigates the demographic effects of the adoption of mobile banking and internet banking. Data collected in the form of a survey of 44 respondents in Jakarta conducted in March 2015. The uniqueness of the study lies in the analysis that weighed between users on a technology-based service Islamic bank with conventional banks.The results showed demographic characteristics banking customers that use technology-based service in Islamic banks so that it can be followed up to the target or marketing communications.Keywords: Mobile Banking, Internet Banking, Sharia Bank, Technology Adaptation, Marketing, Demographic.